(untitled) (Research, Society and Development, 2022)
With the worldwide advance of the Coronavirus Disease pandemic 2019 (COVID-19), there was a need for changes in different food sectors, in order to prevent the spread of this virus. The objective of the work was the elaboration, implementation and implementation of a plan to combat COVID-19 in a Food and Nutrition Unit - UAN hospital in Sobral - CE. The plan was prepared initially following a survey of legislation and guidelines prepared by the competent bodies in order to collect information relevant to the composition of the UAN plan, crossing with the current situation through a checklist of the UAN’s routine before the protocol is implemented and implemented. Then, strategies were developed that followed 3 phases, namely: Individual measures of the team of handlers and everyone who was part of the UAN and who attended it (hospital staff and patients’ companions); Adequacy and monitoring of the environment; Way of preparing and distributing food to better guide the characterization of the protocol. The contingency plan made it possible to observe the necessary changes in the UAN, demonstrating effectiveness in relation to the care provided at the unit, in order to minimize the risks of contamination of COVID-19, due to the intensification of safety measures that were implemented. It is concluded that the elaboration of the plan was fundamental in the UAN in view of the current situation, as it is an environment with an easy chance of contamination of COVID-19, and it is necessary to guarantee everyone’s safety, as the maintenance of life is of paramount importance.